2022
DOI: 10.1038/s41585-022-00626-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends in human semen quality

Abstract: Over the past four decades, studies of various designs have reported spatial and temporal trends in human semen quality. Several standardized-methodology studies in homogeneous populations that compare specific cities within a country or a continent provide clear evidence of geographical differences in sperm production, even over short distances within the same country. Human sperm production is widely believed to be declining over time, but evidence from the scientific literature is less clear. Studies based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 185 publications
0
21
0
1
Order By: Relevance
“…Nigeria also had significantly lower sperm concentration compared to South Africa which is of mixed races. It is not clear if our findings are of any racial correlations, however, Auger et al, reported that black men had significantly lower sperm concentrations than white men and Hispanics 44 . Furthermore, exposure to the pesticide, DDT [1,1,1-trichloro-2,2-bis (chlorodiphenyl)ethane] and its main metabolite, p,p′-dichlorodiphenyl-dichloroethylene (p,p′-DDE) has been associated with the declining trend of semen quality in malaria stricken parts of African countries 45 .…”
Section: Discussionmentioning
confidence: 60%
“…Nigeria also had significantly lower sperm concentration compared to South Africa which is of mixed races. It is not clear if our findings are of any racial correlations, however, Auger et al, reported that black men had significantly lower sperm concentrations than white men and Hispanics 44 . Furthermore, exposure to the pesticide, DDT [1,1,1-trichloro-2,2-bis (chlorodiphenyl)ethane] and its main metabolite, p,p′-dichlorodiphenyl-dichloroethylene (p,p′-DDE) has been associated with the declining trend of semen quality in malaria stricken parts of African countries 45 .…”
Section: Discussionmentioning
confidence: 60%
“…In numerical terms, a systematic review and meta regression analysis by Levine et al involving 185 studies that accounted complexively 42,935 men from unselected Western countries, estimated a variation of −0.70×10 6 cells/mL per year in sperm concentration and −5.33×10 6 cells per year in total sperm count/ejaculate over the period of time between 1973 and 2011 ( Bahadur G et al, 1996 ; Levine et al, 2017 ). An exhaustive discussion of this topic, highlighting major strengths, criticisms, and claims of a possible causal relationship between sperm count, lifestyle, and environmental factors is provided in the review by Auger et al (2022 ). In any case, a strong parallelism is evident between the environmental modifications associated with human activities following the industrial revolution and the variations in the seminal parameters documented in the same period of time ( Auger et al, 2022 ; Damon Matthews and Wynes, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…An exhaustive discussion of this topic, highlighting major strengths, criticisms, and claims of a possible causal relationship between sperm count, lifestyle, and environmental factors is provided in the review by Auger et al (2022 ). In any case, a strong parallelism is evident between the environmental modifications associated with human activities following the industrial revolution and the variations in the seminal parameters documented in the same period of time ( Auger et al, 2022 ; Damon Matthews and Wynes, 2022 ). The global nature of climatic warming, therefore, raises doubts about the possible role of ambient temperature as an environmental interferent on the quality of human semen as an index of testis function.…”
Section: Introductionmentioning
confidence: 99%
“…These hormone levels often fluctuate along a lifespan, which may lead to organismal decay and infertility when they decrease. Thus, an increase in age in males has a significant negative impact on testicular function, sperm functionality and, consequently, fertilization [1,2]. Gamete quality is also impaired by an imbalance in the redox status [3] and the continuous accumulation of genetic mutations [4,5], including Y-chromosome microdeletions [6] and DNA alterations [7] with reduced repair capacity [8].…”
Section: Introductionmentioning
confidence: 99%